2008
DOI: 10.1152/ajplung.00240.2007
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of selective and nonselective Na+ conductances in H441 human airway epithelial cells

Abstract: Brown SG, Gallacher M, Olver RE, Wilson SM. The regulation of selective and nonselective Na ϩ conductances in H441 human airway epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 57 publications
5
41
0
Order By: Relevance
“…5d) and regression analysis showed that G Na (601± 220 pS cell −1 ) accounted for 33.8±7.0% of the total membrane conductance at physiologically relevant potentials. The magnitude of this glucocorticoid-induced conductance is, therefore, essentially identical to that documented in previous studies in which H441 cells were exposed to dexamethasone for 24-48 h [11,13] and is, therefore, clear that the dexamethasone-induced increase in G Na is fully developed after only 2-3 h. Figure 5e shows currents recorded from cells that had been stimulated with dexamethasone (0.2 μM, 2-3 h) in the presence of LY294002 (50 μM). Since the effects of LY294002 upon PI3K are reversible, this compound was present in all bath solutions used in these experiments.…”
Section: Ndrg1-thrsupporting
confidence: 84%
See 4 more Smart Citations
“…5d) and regression analysis showed that G Na (601± 220 pS cell −1 ) accounted for 33.8±7.0% of the total membrane conductance at physiologically relevant potentials. The magnitude of this glucocorticoid-induced conductance is, therefore, essentially identical to that documented in previous studies in which H441 cells were exposed to dexamethasone for 24-48 h [11,13] and is, therefore, clear that the dexamethasone-induced increase in G Na is fully developed after only 2-3 h. Figure 5e shows currents recorded from cells that had been stimulated with dexamethasone (0.2 μM, 2-3 h) in the presence of LY294002 (50 μM). Since the effects of LY294002 upon PI3K are reversible, this compound was present in all bath solutions used in these experiments.…”
Section: Ndrg1-thrsupporting
confidence: 84%
“…5a) showed that V m was normally −60.4±3.7 mV and lowering [Na + ] o had no effect upon V m ( Fig. 5a; V m =−61.0±4.1 mV), indicating that G Na is negligible under these conditions [see also 11,13]. Further analysis confirmed this conclusion by showing that I Na was negligible across the entire range of potentials tested (Fig.…”
Section: Ndrg1-thrmentioning
confidence: 67%
See 3 more Smart Citations